PENGARUH BEBAN KERJA, DISIPLIN KERJA DAN KONDISI KERJA TERHADAP KINERJA KARYAWAN PADA PT. KERETA API DIVRE 1 SUMATERA UTARA - Sinaga, Sara Romatua; Sihombing, Sarimonang (Jurnal Manajemen dan Bisnis, 2021)
Abstract This study aims to determine and explain the effect of workload and work discipline as well as working conditions on employee performance at PT. North Sumatra Divre 1 Train. The analysis method used is multiple linear regression. The population in this study were employees of the Locomotive Dipo, amounting to 36 people. The sample uses saturated sampling or census. Data collection techniques using questionnaires, interviews and documentation study. The results of this study indicate that the workload of work discipline and working conditions have a positive and significant effect on employee performance at PT. North Sumater 1st Regional Railway. Partially, workload, work discipline and working conditions have a positive and significant effect on employee performance at PT. North Sumatra Divre 1 Railway. The coefficient of determination (R square) is 0.891, meaning that variations in employee performance can be explained by workload, work discipline and working conditions by 89.1%, while the remaining 10.9% is explained by other factors not explained in this study such as motivation. , work culture, supervision and others. The multiple linear regression equation obtained is Y = 2.880+ 0.508X1 + 0.344X2 + 0.489X3 + ei, meaning that workload, work discipline and working conditions have a positive effect on employee performance at PT. North Sumatra Divre 1 Train. Of the three independent variables, workload has a greater influence on employee performance, where the regression coefficient is the greatest, namely 0.508. From the research and discussion, it is better if PT. Kereta Api Divre 1 North Sumatra further improves workload, work discipline and working conditions that exist in PT. North Sumatra Divre 1 Train.